Perspectives rituelles dans les Plaines et sur la Côte Nord-Ouest - Klaus Hamberger (Journal de la Société des Américanistes)
Via a transformational analysis of the historical Plains and Northwest Coast seasonal rituals, the article seeks to explore the dynamic logic of North Amerindian social space. We shall endeavor to show that the architecture of the « Sun Dance » and the « Winter Ceremonial » not only served to create a virtual space centered on the polarity between the positions of predator (above) and prey (below), but also to invert these positions by a transformation of perspectives. This perspectival transformation, at the heart of each of the rituals, constitutes also a key to the understanding of the logical connection between them: they construct the same space from two opposite points of view. In the Plains, the ritual aim was to transfer the power of supernatural predators to humans; on the Northwest Coast, to re-transform supernatural predators into human beings. In the first case, the transformation of perspectives was oriented upwards; in the second, downwards. These different orientations are correlated with the seasons in which the rituals took place: summer, a period of mobility where one visited « others » (prey animals, enemies, spirits); or winter, a period of immobility where the (non-human) « others » were received at home. As these different modes of relationship are gendered, the dynamics of ritual space partakes of the seasonal variation of gender relations that characterized native North American social morphology.